Kepemimpinan Pendidikan Islam di Madrasah Aliyah Negeri 2 Kota Sukabumi - Adinda Aulia; Elsa Noviani; Siti Sayidah Mardiyah; Nur Aina Vauziah; Adi Rosadi (CV Edujavare Publishing, 2024)
Leaders of Islamic education must be able to manage organizations well, show strong authority, understand team culture, and treat members well. They must also look at team performance, correct mistakes, encourage positive behavior, and appreciate the advice of others. Qualitative descriptive methods are used to observe and explain the situation of a group of people, subjects, conditions, systems of thought, or recent events, with the aim of presenting detailed descriptions and finding relationships between the phenomena studied. It covers aspects of Islamic education leadership, reflected in the superior school environment and deserves to be used as an example by other educational institutions.